2017
DOI: 10.4279/pip.090008
|View full text |Cite
|
Sign up to set email alerts
|

Dilute antiferromagnetism in magnetically doped phosphorene

Abstract: We study the competition between Kondo physics and indirect exchange on monolayer black phosphorous using a realistic description of the band structure in combination with the density matrix renormalization group (DMRG) method. The Hamiltonian is reduced to a one-dimensional problem via an exact canonical transformation that makes it amenable to DMRG calculations, yielding exact results that fully incorporate the many-body physics. We find that a perturbative description of the problem is not appropriate and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…We have applied the Lanczos transformation method combined with the DMRG [35][36][37] , to study the many-body ground state of a quantum (S = 1/2) impurity (modeled as an Anderson impurity) coupled to the edge of a zigzag nanoribbon of stanene, a slightly buckled (non-planar) honeycomb lattice of Sn atoms, which hosts a topologically protected metallic edge state. The main motivation was to study the detailed spatial structure of the spin correlations between the quantum impurity and the electrons in the host, which characterize the Kondo ground state.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have applied the Lanczos transformation method combined with the DMRG [35][36][37] , to study the many-body ground state of a quantum (S = 1/2) impurity (modeled as an Anderson impurity) coupled to the edge of a zigzag nanoribbon of stanene, a slightly buckled (non-planar) honeycomb lattice of Sn atoms, which hosts a topologically protected metallic edge state. The main motivation was to study the detailed spatial structure of the spin correlations between the quantum impurity and the electrons in the host, which characterize the Kondo ground state.…”
Section: Discussionmentioning
confidence: 99%
“…In order to perform unbiased numerical simulations of the model just described to calculate spin-spin correlations, we use the so-called block Lanczos method recently introduced by the authors 36,37 (see also Ref. 39 for an independent development of the same ideas).…”
Section: Fig 1 (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…The single impurity mapping can be used to study Kondo physics on graphene [79] or multi-band problems such as phosphorene, for instance [80]. It was found that, in the case of graphene, edge states tend to hybridize with the impurity spin introducing a competition between bulk and edge-induced Kondo screening.…”
Section: Applicationsmentioning
confidence: 99%